2016
DOI: 10.1161/strokeaha.115.011599
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Home-Time After Acute Ischemic Stroke in Medicare Beneficiaries

Abstract: Background and Purpose-Stroke survivors have identified home-time as a meaningful outcome. We evaluated home-time as a patient-centered outcome in Medicare beneficiaries with ischemic stroke in comparison with modified Rankin Scale (mRS) score at 90 days and at 1 year post event. Methods-Patients enrolled in Get With The Guidelines-Stroke (GWTG-Stroke) and Adherence Evaluation After Ischemic Stroke-Longitudinal (AVAIL) registries were linked to Medicare claims to ascertain home-time, defined as time spent aliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 18 publications
8
86
0
1
Order By: Relevance
“…For most lay persons, interpretation of treatment effect, summarized as a gain or loss in home time, is more intuitive than relative risks or hazard ratios. For these reasons, home time has been examined in relation to mortality in heart failure [3][4][5] as well as global disability and modified Rankin score in stroke [6][7][8][9][10][11] in administrative claims data sets. For example, warfarin therapy in Medicare beneficiaries with atrial fibrillation who were hospitalized for ischemic stroke was associated with a 48-day gain in home time over 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most lay persons, interpretation of treatment effect, summarized as a gain or loss in home time, is more intuitive than relative risks or hazard ratios. For these reasons, home time has been examined in relation to mortality in heart failure [3][4][5] as well as global disability and modified Rankin score in stroke [6][7][8][9][10][11] in administrative claims data sets. For example, warfarin therapy in Medicare beneficiaries with atrial fibrillation who were hospitalized for ischemic stroke was associated with a 48-day gain in home time over 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the number of days alive and spent out of hospitals and skilled nursing facilities (SNFs) in a given time period, also known as "home time," has been proposed as a measure of quality of life. 2 Home time can be conveniently obtained from administrative claims data and has been endorsed by patients as a meaningful health outcome, [3][4][5][6][7][8][9][10][11] and it can be more intuitively understood. However, not all hospitalizations and SNF stays represent poor health or low quality of life in older adults.…”
mentioning
confidence: 99%
“…It has been shown that patients with an mRS of 3 have significantly more time at home, thus reducing the need for rehabilitation and costs for society [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…with the modified Rankin Scale or the Barthel Index. [11][12][13][14][15]36,39,40 Here, we demonstrate a strong correlation with another measure of functional status, the FIM, adding weight to the construct validity of 'home-time'. Total FIM and motor subscale scores were strongly associated with 'home-time', whereas the correlation between cognitive subscale scores and days spent at home was more moderate.…”
Section: Previous Results Demonstrate That 'Home-time' Correlatesmentioning
confidence: 83%
“…'Home-time' measures the number of days spent at home after stroke onset, taking into account patient survival and days spent in hospital, reflecting a patient's capacity to return to their private residence after hospitalisation. [11][12][13][14][15] 'Home-time' therefore can be unobtrusively and objectively measured using routinely collected data that are linked to health records following stroke and is proposed as a patient-centred surrogate measure of functional status. 'Home-time' in stroke is often measured within 90 days of admission, [11][12][13][14][15] in keeping with the gold-standard follow-up period for clinical trials and epidemiological research.…”
mentioning
confidence: 99%